tudi Kelayakan dan Perancangan Aplikasi Pencarian Buku pada Katalog Perpustakaan Menggunakan Rocchio Relevance Feedback - Albert Albert; Marcel Bonar Kristanda; Seng Hansun (Ultimatics : Jurnal Teknik Informatika, 2016)
A catalog is a register of all bibliographic items found in a library. A bibliographic item can be any information entity. The library catalog has evolved from manual, website based catalog to mobile catalog. Unfortunately, there are still many obstacles in the results of library catalog search, including the relevant results of documents based on input from the user. The purpose of this research is to make the library catalog based on mobile application in android using relevant calculation used rocchio relevance feedback method. Terms— android, library, library catalog, mobile, rocchio.